USAGE OF THE LATEST INNOVATIVE METHODS IN TEACHING ENGLISH VOCABULARY BY EFL TEACHERS. - Fazliddinova Zulfiyakhon Dilmurod qizi (Western European Studies, 2025)
This research aims to explore the recent methodologies used by English teachers in primary school classes. Teaching vocabulary is the most essential directions in TEFL, because with the help of vocabulary learners express their feelings and ideas, and implement the main purpose of language learning process. The study was conducted within the answers collected from survey of different English teachers. The key findings of this study is that daily used methods of English teachers is gamification and TPR, and they are thought to be most effective in the lesson
Keywords: innovative methods; EFL learners